2014
DOI: 10.2149/tmh.2013-19
|View full text |Cite
|
Sign up to set email alerts
|

Ascaris lumbricoids Infection as a Risk Factor for Asthma and Atopy in Rural Bangladeshi Children

Abstract: Controversy persists as to whether helminth infections cause or protect against asthma and atopy. The aim of this study was to investigate the effects of helminth infection on asthma and atopy among Bangladeshi children. A total of 912 children aged 4.5 years (mean = 54.4, range = 53.5–60.8 months) participated in a cross-sectional study nested into a randomized controlled trial in Bangladesh. Ever-asthma, ever-wheezing and current wheezing were identified using the International Study of Asthma and Allergies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 37 publications
4
25
2
Order By: Relevance
“…25 Furthermore, a 2008 study reported a 19.7% prevalence of current wheezing in the same area among 5-year old children. 18 In contrast to these trends, the present study found a significant decrease in the prevalence of wheezing. During the period between 2001 and 2016, we found substantial changes in the socioeconomic status.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…25 Furthermore, a 2008 study reported a 19.7% prevalence of current wheezing in the same area among 5-year old children. 18 In contrast to these trends, the present study found a significant decrease in the prevalence of wheezing. During the period between 2001 and 2016, we found substantial changes in the socioeconomic status.…”
Section: Discussioncontrasting
confidence: 99%
“…In one of our studies conducted later, we reported that the prevalence of current wheezing was 16% in 2001 among children aged 5 to 6 years in a rural area . Furthermore, a 2008 study reported a 19.7% prevalence of current wheezing in the same area among 5–year old children . In contrast to these trends, the present study found a significant decrease in the prevalence of wheezing.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…A subsequent study conducted in 2000 among the schoolchildren aged 6–7 years documented 9.1% of current wheezing 5. Our later research reported a further increase to a 16% prevalence of current wheezing in 2001 among children aged 5–6 years in a rural area 2, while a 2008 study described a 19.7% prevalence of current wheezing in the same area among 5‐year‐old children 3. This sudden increase of the prevalence from 2000 to 2001 and the subsequent slow increase between 2001 and 2008 also attracts our attention.…”
mentioning
confidence: 73%
“…A study performed later in the same area of Bangladesh in 2008, when the infection prevalence was 17.4%, reported that anti‐ Ascaris IgE was associated with increased risk of ever asthma in 5‐year‐old children as well 3. These findings suggest that anti‐ Ascaris IgE is associated with increased risk of wheezing regardless of exposure levels to Ascaris .…”
mentioning
confidence: 90%